Effects of Incorporating Rambutan Juice on the Development, Physicochemical and Sensory Acceptance of Nata de Coco (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Malaysia produces approximately 80,000 tonnes of rambutan annually during the harvesting season, yet its consumption remains largely limited to raw fruit, underscoring the need for innovation and diversification in rambutan-derived food products. This research investigates the feasibility of using rambutan juice as an alternative to coconut water for producing nata de coco, with a focus on maintaining product yield, physicochemical properties, and sensory acceptance. Fermentation media with different ratios of coconut water to rambutan juice were prepared as follows: 100:0 (control), 75:25, 25:75, and 0:100. The mixtures were fermented at room temperature for 21 days, after which the nata was harvested and analyzed for thickness, wet weight, physicochemical properties (moisture and fiber content), texture, color, and sensory acceptance. The study found that higher concentrations of rambutan juice increased both the thickness and yield of nata film. Nata produced with 100% rambutan juice showed significantly greater thickness compared to that made with 100% coconut water. Both 75% and 100% rambutan juice resulted in significantly higher yields than the control, with these ratios producing nata characterized by a harder, chewier, and gummier texture. The addition of rambutan juice did not significantly affect the color of the nata, but it did significantly increase its crude fiber and moisture content. Sensory acceptance of nata made with rambutan juice was comparable to traditional coconut water-based nata de coco, establishing it as a viable alternative for future production. This study demonstrates that rambutan juice serves as an effective and functional alternative to coconut water in nata production, enhancing yield, texture, and nutritional value, especially in terms of crude fiber, while maintaining consumer appeal.
Keywords: Nata de coco; Rambutan juice; Bacterial cellulose; Physicochemical; Sensory acceptance